2014
DOI: 10.3109/02713683.2014.907431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Age-Related Macular Degeneration: Korean National Health and Nutrition Examination Survey 2008–2011

Abstract: The present study provides the first population-based data on the prevalence of and risk factors for AMD in a representative Korean population. The prevalences of early- and late-AMD in this population were 6.0 and 0.6%, respectively. The prevalence of AMD in Koreans is higher than for those in other Asian countries and similar to that of Caucasians in Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The prevalence of early AMD in the present study was similar to the pooled prevalence in European ancestry (11.19%, 95% CI 5.63% to 20.39%)3 and generally higher than that in most Asian countries. Within Asia specifically, prevalence of early AMD was reported at 4.1%–22.8% in Japan,5–8 1.4%–9.5% in China,9 10 14.8% in Taiwan,11 6.0% in South Korea,12 5.1% in Singapore13 and 16%–21% in India 14. In addition to Kumejima, a high prevalence of early AMD was reported at 12.7% in Hisayama Town on the island of Kyushu in southwest Japan5 and at 14.8% in Puzih City, Taiwan,11 approximately 1500 km from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of early AMD in the present study was similar to the pooled prevalence in European ancestry (11.19%, 95% CI 5.63% to 20.39%)3 and generally higher than that in most Asian countries. Within Asia specifically, prevalence of early AMD was reported at 4.1%–22.8% in Japan,5–8 1.4%–9.5% in China,9 10 14.8% in Taiwan,11 6.0% in South Korea,12 5.1% in Singapore13 and 16%–21% in India 14. In addition to Kumejima, a high prevalence of early AMD was reported at 12.7% in Hisayama Town on the island of Kyushu in southwest Japan5 and at 14.8% in Puzih City, Taiwan,11 approximately 1500 km from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Within East Asia, population or cohort-based studies conducted in Japan,5–8 China,9 10 Taiwan,11 South Korea,12 Singapore,13 and India14 show a prevalence of 1.4%–22.8% for early AMD and 0.2%–7.3% for late AMD. In Japan, two population-based surveys5 6 and two cohort studies7 8 have investigated the prevalence of and factors associated with AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Several population-based studies on the prevalence of AMD have been performed in Asia. Prevalence estimates for early AMD and late AMD range from 2.5%–13.8% to 0.2%–7.0%, respectively, with higher prevalence in older study populations [3,11,12,13,14,15,16,17,18,19,20,21,22,23]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Age is the most consistent risk factor for both early and late AMD, but may merely reflect the long latent period of the disease. Systemic risk factors that have been associated with increased risk of AMD in Asians include smoking [9,12,19,22,35,36], male gender [11,35], hypertension [12,15,21,35], hyperlipidemia [15], high levels of high density lipoprotein (HDL) [12,21], chronic kidney disease (CKD) [35], Hepatitis B surface antigen (HBsAg) positivity [12], liver cancer [37], coronary heart disease [19] and increased serum white blood cell levels. High levels of serum triglycerides [21], body mass index within the range of 24–28 [19] and alcohol consumption [13] were protective for early AMD while 25-hydroxyvitamin D (in males only) was protective for late AMD [38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several previous studies reported the prevalence of early and late AMD in the Korea population using different time periods of the Korea National Health and Nutrition Examination Survey (KNHANES) [16][17][18]. The prevalence of early and late AMD ranged between 6.0% and 6.7% and between 0.6% and 0.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%